(¬X ≡ Y) → Z
(X ⊕ Y) → Z
(¬X ∧ Y ∨ X ∧ ¬Y) → Z
(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) → Z
¬(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) ∨ Z(¬X ≡ Y) → Z
(X ⊕ Y) → Z
(¬X ∧ Y ∨ X ∧ ¬Y) → Z
(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) → Z
¬(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) ∨ Z(¬X ≡ Y) → Z
(X ⊕ Y) → Z
(¬X ∧ Y ∨ X ∧ ¬Y) → Z
(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) → Z
¬(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) ∨ Z(¬X ≡ Y) → Z
(X ⊕ Y) → Z
(¬X ∧ Y ∨ X ∧ ¬Y) → Z
(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) → Z
¬(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) ∨ Z(¬X ≡ Y) → Z
(X ⊕ Y) → Z
(¬X ∧ Y ∨ X ∧ ¬Y) → Z
(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) → Z
¬(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) ∨ Z(¬X ≡ Y) → Z
(X ⊕ Y) → Z
(¬X ∧ Y ∨ X ∧ ¬Y) → Z
(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) → Z
¬(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) ∨ Z(¬X ≡ Y) → Z
(X ⊕ Y) → Z
(¬X ∧ Y ∨ X ∧ ¬Y) → Z
(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) → Z
¬(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) ∨ Z(¬X ≡ Y) → Z
(X ⊕ Y) → Z
(¬X ∧ Y ∨ X ∧ ¬Y) → Z
(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) → Z
¬(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) ∨ Z(¬X ≡ Y) → Z
(X ⊕ Y) → Z
(¬X ∧ Y ∨ X ∧ ¬Y) → Z
(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) → Z
¬(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) ∨ Z(¬X ≡ Y) → Z
(X ⊕ Y) → Z
(¬X ∧ Y ∨ X ∧ ¬Y) → Z
(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) → Z
¬(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) ∨ Z(¬X ≡ Y) → Z
(X ⊕ Y) → Z
(¬X ∧ Y ∨ X ∧ ¬Y) → Z
(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) → Z
¬(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) ∨ Z(¬X ≡ Y) → Z
(X ⊕ Y) → Z
(¬X ∧ Y ∨ X ∧ ¬Y) → Z
(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) → Z
¬(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) ∨ Z(¬X ≡ Y) → Z
(X ⊕ Y) → Z
(¬X ∧ Y ∨ X ∧ ¬Y) → Z
(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) → Z
¬(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) ∨ Z(¬X ≡ Y) → Z
(X ⊕ Y) → Z
(¬X ∧ Y ∨ X ∧ ¬Y) → Z
(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) → Z
¬(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) ∨ Z(¬X ≡ Y) → Z
(X ⊕ Y) → Z
(¬X ∧ Y ∨ X ∧ ¬Y) → Z
(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) → Z
¬(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) ∨ Z(¬X ≡ Y) → Z
(X ⊕ Y) → Z
(¬X ∧ Y ∨ X ∧ ¬Y) → Z
(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) → Z
¬(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) ∨ Z(¬X ≡ Y) → Z
(X ⊕ Y) → Z
(¬X ∧ Y ∨ X ∧ ¬Y) → Z
(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) → Z
¬(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) ∨ Z(¬X ≡ Y) → Z
(X ⊕ Y) → Z
(¬X ∧ Y ∨ X ∧ ¬Y) → Z
(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) → Z
¬(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) ∨ Z(¬X ≡ Y) → Z
(X ⊕ Y) → Z
(¬X ∧ Y ∨ X ∧ ¬Y) → Z
(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) → Z
¬(¬(X ∨ ¬Y) ∨ ¬(¬X ∨ Y)) ∨ Z(¬X ≡ Y) → Z
(X ⊕ Y) → Z
(¬X ∧ Y ∨ X ∧ ¬Y) → Z
Объяснение:
T=10;
var
n,m,s:integer;
Y:array[0..T,0..T] of integer;
begin
s:=0;
for n:=0 to T do
for m:=0 to T do
readln(Y[n,m]);
for n:=0 to T do
for m:=0 to T do
s:=s+Y[n,m];
writeln('Сумма:'s);
end.
Если длина массива нужна другая, просто замените значение константы "T"